2021
DOI: 10.3389/fcell.2021.663130
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Activity Is Associated With PD-L1 Downregulation in Thyroid Cancer

Abstract: Thyroid cancer is the most prevalent endocrine malignancy in the United States with greater than 53,000 new cases in 2020. There is a significant gender disparity in disease incidence as well, with women developing thyroid cancer three times more often than men; however, the underlying cause of this disparity is poorly understood. Using RNA-sequencing, we profiled the immune landscape of papillary thyroid cancer (PTC) and identified a significant inverse correlation between androgen receptor (AR) levels and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Thus, a combination of immune-modulatory agents with pro-senescence agents, apoptosis inducers, and SASP modulators should be considered when evaluating pro-senescence modalities as a tool for effective cancer management. Further, we have observed that AR activation decreases the expression of PDL-1 in 84E7 and K1-lentiAR cells, rendering cells more susceptible to immune destruction by T cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a combination of immune-modulatory agents with pro-senescence agents, apoptosis inducers, and SASP modulators should be considered when evaluating pro-senescence modalities as a tool for effective cancer management. Further, we have observed that AR activation decreases the expression of PDL-1 in 84E7 and K1-lentiAR cells, rendering cells more susceptible to immune destruction by T cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the generation of AR-transfected cell lines 84E7, K1-lentiAR, and 8505C-lentiAR [ 21 , 43 ]. Briefly, 84E7 cells were derived through the transfection of 8505C cells with pcDNA3.1 containing the androgen receptor, followed by selection and clonal isolation [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining ASF1B expression levels could be considered a high priority for predicting the efficacy of PD-L1 targeted therapy. Two recent studies show a role for androgens in PD-L1 expression (62) and cell proliferation (63). Both show evidence of a protective role for androgen signaling in thyroid cancer.…”
Section: Discussionmentioning
confidence: 95%
“…In many gender disparity tumors, such as HCC or thyroid, AR bind the PD-L1 promotor and so downregulates PD-L1 expression [ 22 , 23 ]. Guan et al [ 24 ] noted that blocking AR and PD-L1 correlated with a reduction in prostate tumor growth, which provides a connection between androgens and therapy resistance.…”
Section: Introductionmentioning
confidence: 99%